2021
DOI: 10.1007/s40140-021-00475-0
|View full text |Cite
|
Sign up to set email alerts
|

Pain Management in Children During the COVID-19 Pandemic

Abstract: Purpose of Review For many children, the SARS-CoV-2 pandemic has impacted the experience and treatment of their pain. This narrative review draws from the pain literature and emerging findings from COVID-19 research to highlight potentially meaningful directions for clinical consideration and empirical inquiry in the months and years to come. Recent Findings COVID-19 has been linked to diffuse acute pains as well as chronic pain sequelae. Contextual factors known to increase vulnerability for pain and associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 68 publications
3
11
0
Order By: Relevance
“…Multimodal approaches to pediatric pain management have been shown to have reduced side effects compared with a single method. In addition, interdisciplinary approaches have been shown to be the most effective for managing chronic pain [16]. We also found that learning coping skills such as guided imagery, progressive muscle relaxation, and mindfulness-based learning were extremely helpful in managing chronic pain in our patients.…”
Section: Discussionmentioning
confidence: 53%
“…Multimodal approaches to pediatric pain management have been shown to have reduced side effects compared with a single method. In addition, interdisciplinary approaches have been shown to be the most effective for managing chronic pain [16]. We also found that learning coping skills such as guided imagery, progressive muscle relaxation, and mindfulness-based learning were extremely helpful in managing chronic pain in our patients.…”
Section: Discussionmentioning
confidence: 53%
“…Beginning in March 2020, the world saw pediatric pain management clinics abruptly changing their delivery of care owing, in part, to social-distancing requirements. Depending on the location, some healthcare professionals (HCPs) were unable to see patients for varying periods of time because of clinic shutdowns or redeployment, whereas others were able to rapidly pivot to a virtual model of care delivery [ 11 , 12 , 13 ]. Fortunately, across Canada, all 13 pediatric pain clinic sites were able to successfully transition to virtual care, where the largest program in Canada (The Hospital for Sick Children) transitioned over the course of 2 weeks at the onset of the pandemic [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, given that the optimal paradigm for chronic pain management involves psychological, physical, and pharmacological approaches, the transition from in-person care to a full-scale virtual model was no easy feat [ 15 , 16 ]. Multidisciplinary treatment (MDT) teams consisting of physicians (e.g., anesthesiologist, pain doctor, or pediatrician), physical therapists, nurse practitioners, psychologists and/or psychiatrists, occupational therapists, and/or social workers began to rapidly navigate virtual technology to ensure that patients received safe and quality care [ 13 , 17 ]. While some HCPs had prior knowledge of and practice delivering occasional telemedicine appointments, very few had experience delivering full-time remote services (e.g., videoconference, telephone consultation) [ 12 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the early weeks of the COVID-19 pandemic, virtually-delivered care transitioned from being an innovative service delivery method to an essential healthcare platform. Providing healthcare using telehealth enabled pediatric chronic pain clinics to increase patient and staff safety while ensuring continuity of care [1,2]. The expansion of telehealth was further supported by state and federal policy changes, including the Medicaid telehealth expansion, that lifted telehealth restrictions and established parity in reimbursement…”
Section: Introductionmentioning
confidence: 99%